Health systems determinants of delivery and uptake of maternal vaccines in low and middle-income countries: A qualitative systematic review - Davies, Bronte (Department of Public Health and Family Medicine, 2023)
Maternal vaccination has been widely recognised as a key component of the comprehensive package of antenatal care aimed at improving maternal and child health. Low- and middle-income countries (LMICs) are currently falling short of maternal and neonatal mortality targets, with gaps in quality health coverage and a high burden of vaccine-preventable diseases that affect both maternal and child health (MCH). There is a variety and increase of grey and published literature in recent years from LMICs on maternal vaccination programmes and their importance in addressing these gaps in MCH. However, there is a gap in the available literature for research on the role of health systems in the functioning of maternal vaccination programmes, particularly in LMICs. Based on available evidence, understanding health systems determinants of maternal vaccine uptake and delivery requires qualitative insight to inform maternal vaccine programming. A qualitative systematic review was conducted in two phases: a rapid scoping review exploring maternal vaccination and health systems was followed by a systematic review to identify health systems determinants of maternal vaccine delivery and uptake in LMICs. The systematic review was conducted following the Preferred Reporting Items for Systematic Review and Meta-analyses guidelines. Six electronic databases were searched for primary research from LMICs published in English between 2009 and 2021. A qualitative approach to data extraction and evidence synthesis was guided by conceptual health systems framing developed through the scoping review. Thematic analysis identified key descriptive and analytical themes to explore the health systems barriers and enablers of maternal vaccine delivery and uptake in LMICs. Of the 1 242 records identified through database searches, 47 studies were included in the systematic review from 28 LMICs. The majority of included studies were from the South America region (28/47) and included pregnant women as the primary population study group (38/47). Included literature explored mainly Influenza (25/47) and Tetanus toxoid (18/47) maternal vaccine uptake and delivery. Health systems enablers of maternal vaccine uptake included high level of maternal trust in healthcare providers and policy-makers. Barriers to uptake include out-of-pocket spending for vaccination services. Poor communication of policy and guidelines between policy-makers and public/private healthcare providers was identified as a barrier to vaccine delivery, in addition to reliance on external donor funding for vaccine programme implementation and reliance on paper-based antenatal and vaccination records. Urban residence and shorter travelling times to facilities enabled vaccine uptake during pregnancy, while influence of family and influential community members serves as a barrier to vaccine uptake. Limited healthcare worker capacity and subsequent decreased time spent educating patients is a barrier to both vaccine uptake and delivery for pregnant women. Health systems determinants of maternal vaccine delivery and uptake identified and explored in this review study highlight the need for improved communication of vaccine policy guidelines and safety between healthcare providers, policy-makers, pregnant women and the broader community. Monitoring and reporting systems for vaccine delivery in MCH need to be strengthened to inform service delivery policies. This review study provides a health systems approach to maternal vaccination and contributes to the increasing body of work in MCH that can inform future introduction of new maternal vaccines in LMICs.